2021
DOI: 10.15586/aei.v49i3.179
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of physical fitness and anaerobic capacity in asthmatic and non-asthmatic children

Abstract: Introduction and objective: Asthma, is the most common chronic inflammatory disease in childhood period. It can affect the daily life to an advanced level and may become vital. The purpose of this study is to compare physical fitness and anaerobic capacity in asthmatic children (AC) and non-asthmatic children (NC). Materials and methods: A total of 47 children participated in the study; 25 individuals with mild to moderate asthma and 22 healthy children were assessed. The assessed variables consist pulmonary f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 33 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…Although FEV 1 is an important clinical parameter, according to our results, it does not influence the VO 2 peak achieved, at least for patients with mild-to-moderate impairments. In asthmatic children and adolescents, previous studies reported no significant correlations between FEV 1 and exercise capacity 13 , while others found a positive correlation 14 . For children and adolescents with CF, some studies found a positive correlation between FEV 1 and exercise capacity, while others reported that VO 2 peak could be preserved until FEV 1 falls below the predicted 60% 35 .…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Although FEV 1 is an important clinical parameter, according to our results, it does not influence the VO 2 peak achieved, at least for patients with mild-to-moderate impairments. In asthmatic children and adolescents, previous studies reported no significant correlations between FEV 1 and exercise capacity 13 , while others found a positive correlation 14 . For children and adolescents with CF, some studies found a positive correlation between FEV 1 and exercise capacity, while others reported that VO 2 peak could be preserved until FEV 1 falls below the predicted 60% 35 .…”
Section: Discussionmentioning
confidence: 86%
“…The forced expiratory volume in the first second (FEV 1 ) is one of the most used clinical parameters for monitoring CRD, including asthma 2 and CF 3 . Evidence indicates that FEV 1 correlates with clinical worsening and EIB in children and adolescents with asthma 12 , but implications of lung function on reduced exercise capacity are still unclear 13,14 . In patients with CF, evidence suggests that only a part of the variability in exercise capacity can be explained by FEV 1 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Although FEV 1 is an important clinical parameter, according to our results, it does not influence the VO 2 peak achieved, at least for patients with mild‐to‐moderate impairments. In asthmatic children and adolescents, previous studies reported no significant correlations between FEV 1 and exercise capacity, 13 while others found a positive correlation 14 . For children and adolescents with CF, some studies found a positive correlation between FEV 1 and exercise capacity, while others reported that VO 2 peak could be preserved until FEV 1 falls below the predicted 60% 39 .…”
Section: Discussionmentioning
confidence: 96%
“…In asthmatic children and adolescents, previous studies reported no significant correlations between FEV 1 and exercise capacity, 13 while others found a positive correlation. 14 For children and adolescents with CF, some studies found a positive correlation between FEV 1 and exercise capacity, while others reported that VO 2 peak could be preserved until FEV 1 falls below the predicted 60%. 39 Although a significant reduction in FEF 25%-75% was seen in CF patients as compared to asthmatics, it did not seem to affect oxygen consumption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation